Pengaruh Employee Engagement terhadap Organizational Trust melalui Psychological Well-Being dan Transformational Leadership - Fridawati, Yunita Dwi; Nugrohoseno, Dwiarko (Jurnal Ilmu Manajemen, 2021)
The study investigates how the effect of employee engagement on organizational trust and tests whether psychological well-being and transformational leadership mediate the effect of employee engagement on organizational trust. Companies need organizational trust to produce competent human resources so that be able to achieve company goals. Previous research found that employee engagement affects organizational trust and is mediated by psychological well-being and transformational leadership. Therefore, the research here wants to test the effect of an employee on organizational trust and whether psychological well-being and transformational leadership. The population in this study are 90 employees at PT Kereta Api Indonesia Daop 8 in Surabaya using the snowball sampling method in data collection. The results of the structural model are that employee engagement has a significant impact on organizational trust. Employee engagement has a significant impact on psychological well-being. Employee engagement has a significant impact on transformational leadership; psychological well-being has no significant impact on organizational trust. Transformational leadership has not a significant impact on organizational trust.Â  Employee engagement on organizational trust has not indirect impact by psychological well-being. Employee engagement on organizational trust has not indirect impact by transformational leadership. The managerial implication of this study's result can review the factors that can increase their psychological well-being and transformational leadership on employee engagement. Future research in companies may involve organizational commitment variables, organizational culture variables, and job satisfaction variables because it becomes interesting to involve.